Petrografia, geoquímica, geologia isotópica e geocronologia dos diques máficos do sul do estado do Espírito Santo, Orógeno Araçuaí - Raissa Santiago Mendes (2017)
In the Southeastern Brazilian Coast, mafic dyke swarms crosscut the Precambrian basement, emplaced in important regional NW-SE trending structures such as the Alegre and Piúma lineaments. For a long time, the majority of those dykes were related to West Gondwana break-up and basalt flows of the Paraná-Etendeka igneous province. Recently, however, U-Pb dating suggested that at least some of those dykes were emplaced around 500-490 Ma ago, during the collapse of the Araçuaí Orogen. In order to clarify this issue, we present the first systematic study of mafic dykes in the Southern Espírito Santo State. Our results indicate that dykes emplaced in the same structural lineaments can, in effect, be separated in two groups, according to distinct petrographic, geochemical, isotopic and geochronological characteristics. Group 1 dykes are tholeiitic, show moderately fractionated REE, 87Sr/86Sr(i) of 0.7041 0.7065, Nd(t) of -3.4 to -5.5 and TDM between 0.8 and 1.5 Ga. Their mantle sources were shallow (<40 km in depth), probably represented by enriched SCLM (subcontinental lithospheric mantle) in the spinel stability field. Group 2 dykes are alkaline, show highly fractionated REE, higher 87Sr/86Sr(i) of 0.7064 0.7088, more negative Nd(t) < -12 and older TDM around 1.7-1.9 Ga. The mantle sources were deep (>40 km), in the garnet stability field, and they were differentiated through fractional crystallization with very important crustal assimilation. The youngest zircons recovered from the Group 1 dykes yielded a Concordia age of 141.9 ± 1.9 Ma, linking this group with syn-rift evolution of the Phanerozoic Brazilian Coast Basins. On the other hand, the youngest zircons from the Group 2 dykes yielded a Concordia age of 504.7 ± 6.9 Ma, thus indicating that those alkaline dykes are coeval with the intrusive complexes of the G5 Supersuite. This Group is probably related to crustal delamination and slab break-off following the gravitational collapse phase of the Araçuaí Orogen. Our results suggest that the structural lineaments were active in at least three distinct episodes: first, in the Cambrian, during the Araçuaí Orogen collapse, when they served as conduits for both the G5 Supersuite plutons and alkaline dykes of Group 2; second, during the Upper Jurassic Lower Cretaceous rifting of Gondwana, when they served as conduits for the tholeiitic dykes from Group 1; and third, during the Cenozoic, when they were reactivated as normal faults. This study demonstrates the power of geochemical, isotope and geochronological analysis for understanding the evolution and geodynamic context of mafic dyke swarms, especially in areas with overlapping mafic magmatism episodes developed in distinct tectonic settings, coming from distinct sources and differentiated through distinct processes in time and space.